NIMG-04. LONGITUDINAL TRACKING OF PERITUMORAL EDEMA VOLUME USING PACS-INTEGRATED TOOLS PROVIDES CRITICAL INFORMATION IN TREATMENT ASSESSMENT OF NSCLC BRAIN METASTASES AFTER RADIOSURGERY. (14th November 2022) - Kaur, Manpreet; Petersen, Gabriel Cassinelli; von Reppert, Marc; Jekel, Leon; de Santo, Irene Dixe oliveira; Varghese, Sunitha; Chiang, Veronica; Aboian, Mariam
Abstract: PURPOSE: Brain metastases (BM) are the most common intracranial malignancies in adults and mostly originate from lung cancer. Gamma Knife (GK) has become standard of care for BM, however there is insufficient knowledge of the posttreatment volumetric changes of peritumoral edema of BM due to paucity of tools for volumetric segmentation in neuroradiology practice. Recently PACS-integrated tools have become available in select clinical practices facilitating the comparison of posttreatment peritumoral edema volume changes and 2D-based measurements of CE tumor core. METHODS: Patients with NSCLC BM ≥ 10 mm on T1c+ treated with GK had volumetric measurements for up to 7 follow-ups using a PACS-integrated tool that segments the FLAIR hyperintense region surrounding and including the CE lesion. The 2D and volumetric measurements were compared by creating treatment response curves with incorporation of clinical information including steroid timing. RESULTS: 50 NSCLC BM were included. The median pretreatment peritumoral volume was 8.5 cm 3 (IQR 1–47 cm 3, n= 36). The volume significantly decreased at 0–90 days (median 1.2 cm 3, IQR 0.5–6.1 cm 3, n= 31) and between 0-90 and 91-180 days (median 0.8 cm 3, IQR 0.3-2.3 cm 3, n= 26) post-GK. The time of peak median peritumoral volume increase was at > 365 days (median 1.4 cm 3, IQR 0.4–8.1 cm 3, n= 19). There was a positive correlation between longest diameter (LD) and peritumoral edema volume (rs = .75, p< .05). At 181–270 days post-GK 50% of BM showed incongruent response course for LD and peritumoral edema volume. The congruence/incongruence ratio of edema/enhancing portion of BM changed over follow-up time. CONCLUSION: Half of the BM in our study did not show congruent response when comparing posttreatment peritumoral edema volume course to CE lesions in longitudinal assessment. Therefore, there is a critical need for quantitative tools that are incorporated into clinical practice to assess peritumoral edema treatment response.